Immunohistochemical identification of intestinal glucose transporters and glucose uptake during development and maturation of the small intestine of baby alpacas - Rodríguez G., José (2012)
Failures in the absorptive process of monosaccharides during the early postnatal phase at intestinal level, through SGLT-1 and GLUT-2 glucose transporters could lead to animal death. The objective of this study was to determine the hexose transporters SGLT- 1 and GLUT-2 distribution in the gut and its relation with blood glucose levels in baby alpacas. A total of 36 alpacas between 1 to 45 days of age were used. Blood glucose level was determined by enzymatic test and the presence of transporters by immunohistochemistry, using rabbit policlonal antibody anti SGLT-1 and anti GLUT-2. The intensity of the dial (0: no dial, 1; mild dial; 2: strong dial) was evaluated in the axis villus-crypt. The results showed mostly mild dial (degree 1) from the day of birth for the two transporters towards strong (degree 2) by week 2, especially at the jejunum. In addition, SGLT-1 had a greater degree of dial than GLUT-2 in all portions of the intestine at all ages. The blood glucose levels varied from 150 mg/ dL (day 1) to 176 mg / dL (week 5), with significant differences between day of birth and animals at 3 to 5 weeks of age (p<0.05). It is concluded that SGLT1 and GLUT2 are present from birth and this is related to high blood glucose levels at this stage; moreover, the largest presence of these transporters occurs in the jejunum, especially SGLT-1.